2005
DOI: 10.1007/s00429-005-0062-0
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of mucosal immune cells in common carp (Cyprinus carpio L.)

Abstract: The ontogeny of carp (Cyprinus carpio L.) immune cells was studied in mucosal organs (intestine, gills and skin) using the monoclonal antibodies WCL38 (intraepithelial lymphocytes), WCL15 (monocytes/macrophages) and WCI12 (B cells). In addition, recombination activating gene 1 expression was examined in the intestine with real time quantitative PCR and in situ hybridization to investigate extrathymic generation of lymphocytes. WCL38 + intraepithelial lymphocytes (putative T cells) appeared in the intestine at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
(65 reference statements)
2
30
0
Order By: Relevance
“…In mammalian and fish mucosal membranes, intraepithelial leukocytes mainly consist of T cells and some macrophages (Picchietti et al 1997;Zapata & Amemiya, 2000;Huttenhuis et al 2006;Romano et al 2007). In addition, dendritic cells are able to send cytoplasmic protrusions through the epithelium towards the intestinal lumen for antigen recognition and sampling (Rescigno et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian and fish mucosal membranes, intraepithelial leukocytes mainly consist of T cells and some macrophages (Picchietti et al 1997;Zapata & Amemiya, 2000;Huttenhuis et al 2006;Romano et al 2007). In addition, dendritic cells are able to send cytoplasmic protrusions through the epithelium towards the intestinal lumen for antigen recognition and sampling (Rescigno et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cells with lymphoid morphology residing between enterocytes have been observed in carp (Cyprinus carpio; Rombout et al 1993;Romano et al 1998;Huttenhuis et al 2005), sea bass (D. labrax; Abelli et al 1997), rainbow trout (Oncorhyncus mykiss; McMillan and Secombes 1997) and several other teleost species. Within the whole intestinal tract of sea bass, DLT15 + cells outnumber the cells expressing TcRβ.…”
Section: Intestinementioning
confidence: 98%
“…Such cells in mammals directly take up luminal antigen (Brandtzaeg and Pabst 2004;Brandtzaeg et al 2008); however, cells with dendritic appearance (MHC II + ) have been identified in the second gut segment of Atlantic salmon (Koppang et al 2003). It is generally accepted that fish lack an organized GALT and thus contain not follicular lymphoid structures but rather a more diffusely distributed gut-associated lymphoid tissue containing many lymphoid cells, macrophages, eosinophilic and neutrophilic granulocytes (Zapata and Amemiya 2000;Bernard et al 2006a;Huttenhuis et al 2006). Mucosal T lymphocytes represent the major leukocyte population within the teleost gut observed in European sea bass Picchietti et al 1997;Scapigliati et al 2002) and common carp (Rombout et al 1998a) intestine.…”
Section: The Gut-associated Lymphoid Tissuementioning
confidence: 99%
“…As a result, the GALT is rather diffusely distributed in the intestinal mucosa and it is likely that antigenic priming of responses takes place at the site of invasion. Thus, all the important cells of the immune system are generally present in the tissue rather than relying on transport of antigen or cells in and out of the infected site (Zapata and Amemiya 2000;Bernard et al 2006a;Huttenhuis et al 2006). The relatively high expression of MHC II in the gills and in the second segment of the mid intestine is suggestive that these are the major mucosal sites for antigen processing and presentation to prime adaptive responses.…”
Section: Mucosal Immunitymentioning
confidence: 99%